Optimization of Arthrospira platensis growth using organic culture medium - Bualuang, Aporn; Boonburapong, Bongkoj; Laloknam, Surasak (Asia-Pacific Journal of Science and Technology, 2022)
In this study, an organic culture medium for Arthrospira platensis (Spirulina) was created using sugarcane molasses (SGCM), soybean meal (SBM), and small fish bone meal (SFBM) as substitutions for macronutrients and micronutrients in Zarrouk’s medium. Cell growth of A. platensis was monitored using spectrophotometric analysis. The growth patterns of A. platensis under normal and lack of carbon, nitrogen, and micronutrient conditions showed that the optimal growth of a lack of carbon, nitrogen, and micronutrient was decreased by about 50% compared to normal conditions. A singular material was designed to substitute macronutrients and micronutrients in Zarrouk’s medium. In the SGCM medium, the total reducing sugars were varied by concentration in the range of 0 to 3.0% (w/v), while the total protein in the SBM medium was similar. The percentage of dried SFBM in the SFBM medium was also in the concentration range of 0 to 1.0 % (w/v). The results showed that the optimum concentrations of the SGCM, SBM and SFBM media were 0.2% (w/v), 0.5% (w/v) and 0.1% (w/v), respectively. An organic combination medium was designed using optimal concentrations of SGCM, SBM, and SFBM. For a period of 30 days, cell growth of A. platensis was studied and compared to Zarrouk's medium. The wet weights of A. platensis in the combination medium and Zarrouk's medium were 31.25 g and 33.46 g, respectively. The findings indicated that the combination-medium composed of organic substance medium could be used successfully as a culture medium for A. platensis within organic system.